2014
DOI: 10.11646/phytotaxa.177.5.5
|View full text |Cite
|
Sign up to set email alerts
|

A new species and new records of Allium (Amaryllidaceae) for Uzbekistan (Central Asia)

Abstract: Allium decoratum Turginov & Tojibaev is described as new species from Uzbekistan (Central Asia). The distribution area of this species is restricted to Baisuntau moumtains in SW Hissar Range. The new species is close to the type species of subsect. Ligulifolia R.M.Fritsch, but differs from all known species of subsect. Ligulifolia by morphological characters of bulbs and flowers. Also we report 3 Allium species as new records for the territory of Uzbekistan: A. flavellum Vvedensky, A. lutescens Vvedensky a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The genus Allium, a member of Amaryllidaceae family, contains more than 900 species (APG III 2009;Li et al 2010;Tojibaev et al 2014). The most important diversity source of the genus is considered in the mountainous areas of southwest and central Asia including the territory of Iran (Fritsch and Friesen 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Allium, a member of Amaryllidaceae family, contains more than 900 species (APG III 2009;Li et al 2010;Tojibaev et al 2014). The most important diversity source of the genus is considered in the mountainous areas of southwest and central Asia including the territory of Iran (Fritsch and Friesen 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A. viridiflorum was previously considered a local endemic of Arkit, Chatkal range, Kyrgyzstan (Lazkov and Sultanova 2014). A new species population was found in the Uzbekistan part of this IPA site (Tojibaev et al 2014b Note. The genus Anthochlamys comprises five species (POWO, 2022) and is distributed in the Iran-Turanian floristic region (Sukhorukov and Konstantinova 2012).…”
Section: Category Aiimentioning
confidence: 95%
“…Verticillata Tzag., which have whorled leaves (Fritsch 2016). A. viridiflorum differs from A. verticillatum Regel, the type species of the section, by the greenish color of tepals that are nine times longer than the pedicels, short stamens, ecological preference, and geographical distribution (Tojibaev et al 2014b). A. viridiflorum was previously considered a local endemic of Arkit, Chatkal range, Kyrgyzstan (Lazkov and Sultanova 2014).…”
Section: Category Aiimentioning
confidence: 99%
“…The databasing revealed that a significant part of herbarium materials at TASH had not been revised during the preparation of the 'Flora of Uzbekistan' and the compilation of floristic checklists of various regions of Uzbekistan. In course of this inventory, 47 species records new to Uzbekistan were detected as a result of studies on the flora of the South-Western Tian-Shan , Tojibaev et al 2014b, 2014d. As part of the databasing, selected scanning of herbarium specimens is going on (image quality 300 to 600 dpi).…”
Section: Databasingmentioning
confidence: 99%
“…Field work, herbarization, inventory and identification of old herbarium specimens, databasing and digitizing of the national collections are actively going on. During this period, as a result of the extensive fieldwork and the targeted search for unknown taxa in less explored areas, several new species (e.g., , Khassanov & Tojibaev 2009, 2010, Tojibaev & Turginov 2013, Tojibaev et al 2014a, 2014b, Beshko 2015 and even a new genus, Kuramosciadium Pimenov et al (2011: 492), appeared exclusively because of field-based rather than collection-based research. The descriptions of new taxa were published mostly by Uzbek botanists alone or in co-authorship, although foreign researchers also contributed to a minor extent (Sukhorukov 2007, Fritsch 2009, Sennikov 2011, Seregin 2015.…”
Section: Recent Fieldworkmentioning
confidence: 99%